Identification of type III effectors modulating the symbiotic properties of Bradyrhizobium vignae strain ORS3257 with various Vigna species - Pongpan Songwattana (Nature Portfolio, 2021)
Abstract The Bradyrhizobium vignae strain ORS3257 is an elite strain recommended for cowpea inoculation in Senegal. This strain was recently shown to establish symbioses on some Aeschynomene species using a cocktail of Type III effectors (T3Es) secreted by the T3SS machinery. In this study, using a collection of mutants in different T3Es genes, we sought to identify the effectors that modulate the symbiotic properties of ORS3257 in three Vigna species (V. unguiculata, V. radiata and V. mungo). While the T3SS had a positive impact on the symbiotic efficiency of the strain in V. unguiculata and V. mungo, it blocked symbiosis with V. radiata. The combination of effectors promoting nodulation in V. unguiculata and V. mungo differed, in both cases, NopT and NopAB were involved, suggesting they are key determinants for nodulation, and to a lesser extent, NopM1 and NopP1, which are additionally required for optimal symbiosis with V. mungo. In contrast, only one effector, NopP2, was identified as the cause of the incompatibility between ORS3257 and V. radiata. The identification of key effectors which promote symbiotic efficiency or render the interaction incompatible is important for the development of inoculation strategies to improve the growth of Vigna species cultivated in Africa and Asia.